Integration Interconnections of Biology and Islamic in Learning as Efforts to Support Education for Sustainable Development Goals (ESD) - Elvara Norma Aroyandini (Kaunia: Integration and Interconnection Islam and Science, 2018)
The world has faced a quite serious problem, namely decreasing environmental quality. As data released by UNEP in 2011 and 2012, that some indicators of the environmental quality are getting worse as occurs in Indonesia. Indonesia has the second highest biodiversity in the world after Brazil, but before that diversity has been successfully learned and utilized, nature is already damaged. It is marked by the loss of natural forest, coral reef damage, and so on. If there is not immediately respond, the environment will not able to support human life in a sustainable manner. Therefore, inculcation is important as the value to students who will use nature as the next generation. Planting can be realized through education, it is known the Education for Sustainable Development (ESD). One kind of learning is biology which has the same material curriculum and will be integrated with Islamic material. The author hopes that in the next will be born the students who are able to support the sustainability of development. Both because of scientific awareness of science taught through biology or awareness of God's command taught through his fusion with religion. This paper used an explorative writing that is qualitative-descriptive and pure research. The results concluded that the learning of integration-interconnection of Islam and science in biology learning can help the success of Education for Sustainable Development (ESD).